Verbal conditioning and behaviour - Das, J. P. (Jagannath Prasad) (Pergamon Press, 1969)
Verbal Conditioning and Behavior clarifies certain major issues in the area of verbal behavior, with emphasis on the problems that are continuous and those that are discontinuous with animal learning research. This book provides information pertinent to certain areas of complex verbal behavior.